Credit risk management at Vietnam bank for agriculture and rural development - Nguyen, Thi Nguyet Anh (H. : ĐHQGHN, 2020)
Thesis has outlined the problem of credit risk and proposed some solutions to help Agribank gradually improved credit risk management quality. Hopefully with the effective application of supported solutions mentioned in the thesis will help the Bank grow stronger, safer on the roads of integration into the regional and the whole world financial market.